Troubled water - Holman, Ian P.; Knox, Jerry W. (Royal Horticultural Society, 2022)
Water forms the basis of one of the Net Positive for Nature targets within the recent RHS Sustainability Strategy. However, while many gardeners may be aware of the water challenges that faced Cape Town in South Africa as it approached ‘Day Zero’ in 2018 or the 2001–2009 Millennium Drought in Australia, why do the RHS and the UK’s 30 million gardeners need to worry about garden water use?